Stability of monetary unions: Lessons from the break-up of Czechoslovakia - Jan Fidrmuc; Julius Horvath; Jarko Fidrmuc (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
In 1993, Czechoslovakia experienced a two-step break-up. On January 1, the country disintegrated as a political union, while preserving an economic and monetary union. Then, the Czech-Slovak monetary union collapsed on February 8. This paper analyzes the economic background of the two break-ups from the perspective of the optimum currency area literature. The main finding is that the Czech and Slovak economies were vulnerable to asymmetric economic shocks, such as those induced by the economic transition. In particular, the stability of Czechoslovakia was undermined by low correlation of permanent output shocks, low labor mobility and higher concentration of heavy and military industries in Slovakia.
Keywords: F33; F36; F42; 330; Optimum currency areas; Disintegration; Czechoslovakia